Micromorphological and anatomical features of four species of Elytrigia Desv. (Poaceae) - Meng, Lin; Mao, Peichun (Bangladesh Journal of Plant Taxonomy, 2013)
The micromorphological and anatomical characters of Elytrigia caespitosa (K.Koch) Nevski , E. intermedia (Host) Nevski × E. elongata (Host) Nevski, E. intermedia(Host) Nevski and E. repens (L.) Desv. ex Nevski have been studied using Scanning Electron Microscope (SEM) to determine interspecific variation. The results show that the root transverse section consists of epidermis, cortex and stele. Two rings of vascular bundles and a central pith cavity appear in stem morphology. The leaves of E. caespitosa have either single or twin, horse shoe-shaped short cells born along the costal zone of the upper epidermis, which lack prickle hairs and contain spherical or oblique-shaped papillae. In E. intermedia, the parallel subsidiary cells are distributed on the upper epidermis, and there are no short cells in the leaves. Dome-shaped subsidiary cells appear on the upper epidermis of E. intermedia × E. elongata and E. repens, but E. intermedia × E. elongata showes spot-shaped papillae, and its bulliform cells sank into the hinge cells. E. repens has no papillae, and its bulliform cells are not sunken into the mesophyll. Therefore, the differences in micromorphological characters on the upper epidermis of the leaf could be useful in classifying and determining phylogenetic relationships among the species. DOI: http://dx.doi.org/10.3329/bjpt.v20i2.17388 Bangladesh J. Plant Taxon. 20(2): 135-144, 2013